Clinical presentation of Celiac disease among Libyan children : The effect of Exclusive Breastfeeding - Raja Alfakhri,; Amal Alfakhri,; Soad Gargoum, (Scientific Journal of University of Benghazi, 2018)
Celiac disease (CD) is a chronic small intestinal immune-mediated enteropathy triggered by exposure to dietary gluten in genetically susceptible individuals. It is claimed that prolonged breastfeeding is associated with a reduced incidence of symptomatic disease or alteration of its classical presentation. Aims, to explore the effect of EBE during the first 6 months of life on the presentation of celiac disease. Case series study was adopted, the sample was collected from Gastroentrology clinic of Benghazi Pediatric Hospital between 1st November 2011 up to April 2012. The data was collected using a validated questionnaire, Libyan children with proven intestinal biopsy were exclusively included. The data were entered into SPSS version 21. A sample of 100 child with mean age 10.5 years ( ± 4.45 years), 29% male and 71 % female, 37% have positive family history, age of symptoms extends from 4 months to 15 years. The duration of exclusive breastfeeding varies between few days to 18 months, earlier age of starting of gluten was 2 months. At diagnosis the most frequent symptoms were diarrhea and short stature (30% and 25% respectively). Age of diagnosis and mode of presentation do not significantly varies between the breastfed and other children. EBF has no significant correlation neither with age of disease symptoms, age of diagnosis nor with type of disease presentation. Conclusions, The results suggest that EBF does not modify CD in its presentation, neither the age of symptoms nor the age of diagnosis, the sample of this study presented more frequently with diarrhea and short stature.